Refractory thrombocytopenia during liver transplantation requiring splenectomy. Issue 1 (2nd January 2023) - Wilder, Ivana Wrobleski; Reskallah, Alexander; Pivalizza, Catherine M.; Bynon, John S.; Pivalizza, Evan G.
Abstract: Although thrombocytopenia is common in end-stage liver disease, severe, refractory thrombocytopenia during liver transplantation is rare, and if immune based, usually presents months or years later. This case describes an adult woman in whom preoperative evaluation had not determined an immune-related cause of thrombocytopenia. Clot strength was dramatically impaired as measured by thrombelastography during the transplant. Following a lack of response to repeat platelet transfusions, splenectomy was performed after graft reperfusion with rapid temporal restoration of clot strength. This case shows a severe manifestation of perioperative thrombocytopenia during liver transplantation and clinically guided management when measured clot strength is too low for accurate determination.